2013
DOI: 10.1007/s00586-013-2803-8
|View full text |Cite
|
Sign up to set email alerts
|

How do low back pain patients conceptualize their expectations regarding treatment? Content analysis of interviews

Abstract: Purpose The purpose of this study was to gain insight into how low back pain (LBP) patients conceptualize the construct of expectations regarding treatment. Methods This study was nested within a mixed-method randomized clinical trial comparing three primary care interventions for LBP. A total of 77 participants with LBP lasting longer than 6 weeks were included; semi-structured interviews were conducted querying patients about their expectations for treatment. Also factors influencing their expectations were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
33
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 26 publications
4
33
0
Order By: Relevance
“…Our findings are consistent with those of Haanstra et al, who found that patients talked about both “values (what they hoped) and probabilities (what they thought likely)” [30]. …”
Section: Discussionsupporting
confidence: 92%
“…Our findings are consistent with those of Haanstra et al, who found that patients talked about both “values (what they hoped) and probabilities (what they thought likely)” [30]. …”
Section: Discussionsupporting
confidence: 92%
“…Two authors (R.E., M.M.) performed a template style content analysis of the interviews [19][20][21][22]. First, the transcribed texts were independently reviewed to gain a general understanding of the data and establish preliminary codes [10,[19][20][21]23].…”
Section: Discussionmentioning
confidence: 99%
“…Designing studies that reflect the perspective of a patient with LBP would considerable help in understanding the suffering associated with the disease [ 14 ], and the implications it has on the patient’s life [ 21 23 ]. Moreover, these studies would assist professionals in the decision-making process to treat LBP [ 24 26 ], and in understanding the patient’s expectations regarding their treatment [ 4 , 27 29 ], and their respective recovery [ 16 , 30 31 ]. Also, the effect of disability associated with LBP [ 32 ], and the relevance of factors, such as culture, beliefs and the patients’ daily social environment could be ascertained [ 3 , 12 , 19 ].…”
Section: Introductionmentioning
confidence: 99%